1975
DOI: 10.1063/1.322112
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic tensile strength of mercury

Abstract: The dynamic tensile strength of mercury has been determined using very-short-duration (∼100 ns) stress pulses generated by an electron-beam machine. Tensile strengths of 1900 MPa (19 kbar) are observed for mercury at maximum tensile stress rates of ∼75 MPa/ns. These results are somewhat lower than the value of 3000 MPa predicted by homogeneous nucleation theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

1977
1977
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 12 publications
0
24
0
1
Order By: Relevance
“…The liquid fracture pressure increased from 7 to 425 atm by additional cleaning of the mercury. Further experiments [9], performed under controlled conditions with highly purified mercury, show that the fracture pressure is ≈19 katm; very similar to the theoretical limit of 22.3 katm. The overall agreement between mercury experiments and the theory was very good [9].…”
Section: Cavity Appearancementioning
confidence: 79%
See 3 more Smart Citations
“…The liquid fracture pressure increased from 7 to 425 atm by additional cleaning of the mercury. Further experiments [9], performed under controlled conditions with highly purified mercury, show that the fracture pressure is ≈19 katm; very similar to the theoretical limit of 22.3 katm. The overall agreement between mercury experiments and the theory was very good [9].…”
Section: Cavity Appearancementioning
confidence: 79%
“…Experiments to study liquid fracture under negative pressure have been carried out with liquid mercury under various conditions [8,9]. Early experiments of Briggs [8] showed that the fracture pressure has a strong dependence on experimental conditions, i.e., cleanliness of the mercury and the surfaces of the glass tube that contain the liquid.…”
Section: Cavity Appearancementioning
confidence: 99%
See 2 more Smart Citations
“…The fragmentation of liquid at strong negative pressure was investigated in the 1940s and 1970s by several authors who based their work on the Frenkel theory [1][2].…”
Section: Introductionmentioning
confidence: 99%